The varying roles of parents and the cognitive–emotional variables regarding the different types of adolescent prosocial behavior - Mesurado, Belén (2018)
Fil: Mesurado, Belén. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Interdisciplinario de Investigaciones en Psicología Matemática y Experimental; Argentina